The missing link: The significance of institutional interdependencies and dynamics of action for transnational labour regulation in multinational companies - Thomas Haipeter; Sophie Rosenbohm; Christine Üyük (British Journal of Industrial Relations, 2024)
In recent decades, both academic research and industrial relations practice have been increasingly concerned with whether, and to what extent, transnational forms of labour regulation might constitute a countervailing power to globally operating companies. And although numerous studies have analysed the various instruments and institutions of transnational labour regulation – such as Global Framework Agreements, trade union networks and European or World Works Councils – as yet there has been little in the way of exploration of their dynamics or interconnections. Against this backdrop and based on a comparison of three case studies of multinational companies, we focus on what we consider to be the 'missing link' between the dynamics of social action and the interdependencies of institutions in order to explain how transnational institution building can contribute to the development of transnational labour regulation. Specifically, we investigate how different pathways to transnational labour regulation have been the outcomes of actions taken by actors in a multinational corporation and how, in turn, these developments shaped the dynamics of subsequent action. The study underlines that those pathways can only be properly understood when seen in terms of social actors, their power resources and their willingness and capacities to deploy them.
Keywords: 330